(Un)wanted and (Un)sought Services: Exploring the Funeral Industry Positivity and Rural Funeral Directors' Destigmatization. Issue 5 (2nd November 2022) - Bi, Da; Ploeger-Lyons, Nicole A.
ABSTRACT: This study explores the positive nature of the funeral industry in rural communities and examines how rural funeral directors perform community services to destigmatize their profession. Analysis of interviews ( n = 27) with rural funeral directors revealed that the funeral industry, although it is associated with death and dying, was needed and accepted in the community – a phenomenon the article labels (un)wanted and (un)sought services . This construct challenges the denial of death thesis and supports the contingent and discursive nature of death and dying. Moreover, rural funeral directors offer life enrichment programs, support local businesses, work as partial civic servants, and participate in community governance. This study argues that these supportive performances reflect the communicative mechanism of destigmatization, reinforcing the needed and acceptable nature and diminishing the unwanted and unsought nature of the profession. Lastly, the study advocates that urban funeral homes learn from rural funeral homes regarding communal characteristics to make a more supportive and cohesive urban life.